“Pay-as-you-wish” Program As Marketing Communication Strategy Using SOSTAC On Indonesian MSME Business - Syahrul Syahrul; Yohannes Don Bosco Doho; Yasinta Dewi Pradina (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2022)
This project discusses the “Pay-as-you-wish” program as a marketing communication strategy using SOSTAC on Indonesian micro small and medium business enterprises study case in Omnivour. Omnivour, as one of the MSME brands, offers delivery affordable healthy food catering for its customers during Covid-19 pandemic as its business model. However, the brand still lacks awareness. Omnivour is facing the real problem that the operation should run for